Effect of surface treatment in cork reinforced composites - Ben Abdallah, F. (2010)
This work explores the possibility of using cork for reinforcing of polypropylene (PP). The cork granules were mixed with PP by extrusion and the mixture was then injected. The hydrophilic character of cork and the hydrophobic character of PP influence negatively the adhesion at the interface between the reinforcement and the matrix. In order to improve it, several chemical modifications of the cork reinforcements were used in this work: treatment with silane, with sodium hydroxide and with a compatibilizing agent MAPP. The interface modifications were studied by scanning electron microscopy (SEM), Goniometry analysis and infrared spectroscopy analysis (IR). The improvement of the mechanical properties was demonstrated by tensile tests. On their basis it was demonstrated that the best interfacial adhesion between cork and PP is achieved by the silane chemical modification (silanization).